The impact of utilizing recycled EPDM both independently and in conjunction with SBS on the overall characteristics of bitumen - Kok, Baha Vural; Yildirim, Kader; Kayaalp, Bekir Tuna (Springer, 2025)
The rising demand for raw materials and the environmental burden of industrial waste have increased interest in sustainable solutions for asphalt pavement engineering. Recycled ethylene-propylene-diene monomer (EPDM) is a promising modifier that combines thermoplastic resilience with environmental benefits. This study investigates the modification of a 70/100 penetration grade bitumen with EPDM and its co-modification with styrene-butadiene-styrene (SBS). A comprehensive experimental program evaluated conventional properties, rheological behavior, aging resistance, thermal susceptibility, elastic recovery, and microstructural features. Results indicated that EPDM improved softening point by 3-5% and increased viscosity, though it also heightened susceptibility to phase separation. Co-modification with SBS provided more pronounced improvements: high-temperature stiffness (G*/sin delta) rose by up to 25% compared to SBS-only modification, non-recoverable creep compliance decreased by more than 70%, and elastic recovery increased by up to 130%. FTIR analysis further showed about 70% lower oxidation indices in co-modified binders, while BBR testing confirmed that all formulations retained satisfactory low-temperature performance (PG 70-16). Overall, the 10% EPDM + 2% SBS binder achieved the most balanced performance across rutting resistance, elasticity, and oxidative durability.
Keywords: Bitumen; Modification; EPDM; SBS; Rheology